Pengaruh Destination Image dan Tourist Attraction Terhadap Loyalitas Wisatawan Melalui Kepuasan Wisatawan Wisata Halal Makam Syaichona Moh. Cholil Bangkalan - Arvi, Afninda Ainun; Syarif, Muh. (LPPM Institut Pendidikan Nusantara Global, 2025)
Halal tourism is now growing rapidly in Indonesia in line with the increasing interest of Muslim tourists in destinations that offer spiritual and religious value. One of the leading destinations in Bangkalan Regency is the Tomb of Syaichona Moh. Cholil, known for its strong historical and spiritual significance and consistently crowded with visitors. However, the high number of visits does not fully reflect sustainable tourist loyalty, making it necessary to examine the influence of destination image and tourist attraction on loyalty through visitor satisfaction. The purpose of this study is to analyze the influence of destination image and tourist attraction on tourist loyalty, both directly and through tourist satisfaction as a mediating variable. The research employs a quantitative approach. The population of this study consists of tourists visiting the Tomb of Syaichona Moh. Cholil in Bangkalan, with a sample of 100 respondents. Data were collected using purposive sampling with a Likert-scale questionnaire, then analyzed using the Partial Least Square Structural Equation Modeling (PLS-SEM) method through SmartPLS 0.4 software. The results show that destination image and tourist attraction have a positive and significant effect on tourist satisfaction. In addition, tourist satisfaction is proven to have a significant influence on loyalty and serves as a mediating variable between destination image and tourist attraction on tourist loyalty. These findings affirm that strengthening the destination’s image and tourist appeal can enhance satisfaction while encouraging tourist loyalty to religious tourism destinations in Bangkalan Regency.